2009
DOI: 10.1261/rna.1422509
|View full text |Cite
|
Sign up to set email alerts
|

Two Piwi proteins, Xiwi and Xili, are expressed in the Xenopus female germline

Abstract: The Argonaute superfamily is a large family of RNA-binding proteins involved in gene regulation mediated by small noncoding RNA and characterized by the presence of PAZ and PIWI domains. The family consists of two branches, the Ago and the Piwi clade. Piwi proteins bind to 21-30-nucleotide-long Piwi-interacting RNAs (piRNAs), which map primarily to transposons and repeated sequence elements. Piwi/piRNAs are important regulators of gametogenesis and have been proposed to play roles in transposon silencing, DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 56 publications
4
43
0
1
Order By: Relevance
“…Very little is known about transposon silencing in Xenopus . The Piwi proteins, which have been implicated in multiple aspects of germ cell specification and transposon silencing (Houwing et al, 2007), are expressed in Xenopus eggs (Wilczynska et al, 2009) and a Xenopus Piwi homolog (Xiwi) is enriched in the germ plasm (Lau et al, 2009). Also, the small RNAs bound by Piwi proteins (piRNAs) represent the major class of small RNA in Xenopus oocytes (Lau et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Very little is known about transposon silencing in Xenopus . The Piwi proteins, which have been implicated in multiple aspects of germ cell specification and transposon silencing (Houwing et al, 2007), are expressed in Xenopus eggs (Wilczynska et al, 2009) and a Xenopus Piwi homolog (Xiwi) is enriched in the germ plasm (Lau et al, 2009). Also, the small RNAs bound by Piwi proteins (piRNAs) represent the major class of small RNA in Xenopus oocytes (Lau et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1B, we detected expression of all four genes thought to be involved in miRNA biogenesis and function (dicer1, rnasen, eif2c2, eif2c4) in all tissues tested. We recently demonstrated that at least two Argonaute proteins of the Piwi family, piwil1.1/piwil1.2 (also known as Xiwi1a/Xiwi1b), and piwil2 (also known as Xili), are present in Xenopus oocytes (Wilczynska et al 2009). We detected piwil1.2 and piwil2 mRNA in both the germline and the soma; however, no Piwi proteins were detected in the soma (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Third, we previously demonstrated that one Piwi protein of X. tropicalis, piwil1.1/piwil1.2, associated specifically with ;30 nt RNAs in Xenopus oocytes (Wilczynska et al 2009). Next, we validated two of these candidate piRNAs, named piR-1 and piR-2, using Northern blotting.…”
Section: Xenopus Pirnasmentioning
confidence: 96%
“…Neither a mutant of nanos1 with 5Ј sequences non-complementary to the MO (nanos1-mut) nor a control MO with five base changes (Nanos1-Ctrl-MO) had any effect on nanos1 translation (data not shown). We have previously shown that during early developmental stages, Nanos1 is found within germ plasm, colocalizing with the germ plasm marker Xiwi (Lai et al, 2011;Lau et al, 2009;Wilczynska et al, 2009). Importantly, whereas Xiwi was readily detected, Nanos1 protein was not observed in embryos previously injected with Nanos1-MO (20 ng) after staining with anti-Nanos1 and anti-Xiwi antibodies (Fig.…”
Section: Embryos Depleted Of Nanos1 Are Deficient In Pgcsmentioning
confidence: 99%